A Systematic Analysis of Tourism and Hospitality Management Higher Education Curriculum in Bangladesh: Present and Future - Alam, S. M. Shahedul (Journal of Tourism & Adventure, 2025)
Tourism and Hospitality Management (THM) higher education in Bangladesh is still in its early stages and faces significant challenges in curriculum design and implementation. This study adopts a mixed-methods approach, utilizing both primary and secondary data, to conduct a comprehensive analysis of undergraduate THM curricula across seven public universities, one private university, and eight colleges affiliated with the National University. The findings reveal that most THM programs are not outcome-based and lack alignment with the Bangladesh National Qualifications Framework (BNQF) and University Grants Commission (UGC) credit requirements. Additionally, 66.67% of institutions fail to incorporate practical or fieldwork components. There is also a lack of consistency in course offerings, titles, credit allocations, and internship durations. These issues are further compounded by limited industry relevance, poorly structured course hierarchies, and the absence of a standardized national curriculum. In response, the study proposes a Four-Step Strategic Framework to guide curriculum development: (1) Establish uniform national guidelines for THM higher education, (2) Adopt a standardized course structure, (3) Develop essential support facilities, and (4) Implement continuous monitoring and review mechanisms. This framework aims to support faculty members, academic leaders, and policymakers in enhancing the relevance, quality, and coherence of THM education in Bangladesh.